Pengaruh Teknologi Digital Terhadap Pemahaman Generasi Z Tentang Pancasila - Aura Fisqiyah Rahmadillah; Muhammad Aryawinata Sanusi; Nice Electra; Herli Antoni (Student Scientific Creativity Journal, 2025)
The digital era brings challenges to the internalization of Pancasila values, especially among generation Z who are exposed to global information flows and foreign cultures. This research aims to analyze the influence of digital technology on the understanding of Generation Z about Pancasila, especially the third precept, "Unity of Indonesia." Using a qualitative approach and analytical descriptive methods, this study utilizes data from literature and documentation. The results of the study show that Generation Z still respects cultural, ethnic, and religious diversity. However, global cultural influences can shift appreciation of local values. Pancasila-based education and critical literacy play an important role in maintaining the relevance of these values. The use of digital technology as a medium of learning and socialization is considered strategic in strengthening the understanding of Generation Z of Pancasila. In conclusion, the values of Pancasila remain relevant if supported by innovative and technology-based education. This step is important to ensure that generation Z can face globalization without losing their national identity, as well as internalize and apply Pancasila values in daily life.